Perempuan dan HAM: Peta Permasalahan dan Agenda Aksi - Trias Setiawati (Universitas Islam Indonesia, 2002)
Nowadays the world does not understand human rights as realization the individualism and liberalism. Human rights is viewed as human concept that the rights which are inherent in human nature without debating the background of racism, tenacity religion etc. The concept above-mentioned is modern one. In this regard, the issue of woman empowerment, in fact, is still becoming marginalized issue in all fields of development. Thus, the using of gender perspective is needed in all policies, for instance in planning, in organizing, in actuating, in coordinating, and in evaluating the cases of evading human rights. For that reason, the role of man is still needs developing in building a prosperous and just society.